HPV DNA Testing in Cervical Cancer Screening: Challenges, Opportunities, and Future Directions - Dwiza, Mutiara; Aurora, Wahyu Indah Dewi (Scientific Of Environmental Health and Diseases, 2025)
Background: HPV DNA testing is increasingly recommended as a primary method for cervical cancer screening due to its high sensitivity and strong ability to detect high-risk HPV infections associated with cervical cancer. However, implementation remains challenging in many settings, particularly in low- and middle-income countries, due to health system, economic, and sociocultural barriers. This narrative review highlights key challenges, opportunities, and future directions for HPV DNA testing in cervical cancer screening programs. Methods: A narrative review was conducted by searching PubMed, Scopus, and Google Scholar, complemented by relevant guidelines and reports from international organizations such as the World Health Organization (WHO). Keywords included HPV DNA testing, cervical cancer screening, primary HPV screening, self-sampling, and implementation barriers. The evidence was synthesized thematically to summarize major barriers, innovative strategies, and future perspectives. Results: HPV DNA testing offers superior sensitivity compared with cytology and VIA, enabling earlier detection of precancerous lesions and allowing longer screening intervals. Major challenges include limited laboratory capacity, high costs, supply chain constraints, insufficient workforce training, weak referral and follow-up systems, and sociocultural factors such as stigma and low screening acceptance. Key opportunities include HPV self-sampling to expand screening coverage, risk-based triage using HPV genotyping to reduce unnecessary referrals, and digital health integration to improve tracking, monitoring, and continuity of care. Conclusion: HPV DNA testing has strong potential to strengthen cervical cancer screening and support elimination efforts, but successful scale-up requires addressing system-level barriers, ensuring sustainable financing, improving follow-up pathways, and expanding equitable access through innovations such as self-sampling and risk-based strategies.